Sex and the Statehouse: The Law and the American Same-Sex Marriage Debate - Failinger, Marie A. (Dialog, 2009)
Same-sex marriage remains a point of contention in American politics. The recent history of this conflict suggests that the Court's attempt to frame issues of sexual politics through paradigms of the right to choose and the tolerance principle, and constitutional ‘liberty’ and ‘equality’ cases raises difficult questions of justice. This article proposes that a Lutheran response, grounded in an understanding of the orders of creation, might interrogate these assumptions, particularly about the appropriate reach of government in sexual and family matters.